An intention-to-treat-analysis of the efficacy of immunotherapy using Mycobacterium w vaccine and Purified Protein Derivative of Tuberculin for warts with assessment of improvement in quality of life - Mohta, Alpana; Sharma, Manoj Kumar; Kumari, Pramila; Ghiya, Bhikam Chand; Soni, Prasoon; Metha, Rajesh Dutt (Dermatology Practical & Conceptual, 2022)
Introduction: Lately, immunotherapy has evolved as a safe and reliable management option for treatment of warts. Various immunogens among others in use include vaccines and antigens like purified Protein Derivative of Tuberculin (PPD) and mycobacterium w (Mw) or mycobacterium indicum prani vaccines.Objectives: The study was aimed to assess the effectiveness and safety profile of intralesional Mw vaccine against intralesional PPD for the management of multiple warts with assessment of the improvement in quality of life (QoL) using the Dermatology Life Quality Index questionnaire.Methods: Patients aged above 12 years with ≥2 warts were recruited for the study. These individuals were randomized into groups A and B, namely Mw vaccine (group A) and PPD Tuberculin (group B). At each visit, 0.1-0.2 ml of active antigen was infiltrated intralesionally into the largest/mother wart. The injections were repeated after every 4 weeks, for the next 12 weeks. QoL improvement was measured.Results: This intention to treat analysis was completed by 102 patients, of which 55 were in group A and 47 in group B. The rate of complete clearance was comparable in group A (76.3%) with the one in group B (65.9%, P = 0.064). Prior to treatment initiation, the most severely impacted domain of life by warts was ‘symptoms and feelings’. There was a statistically significant improvement in QoL at the end of the treatment ( P <0.01).Conclusions: Mw vaccine holds leverage over PPD with a marginally higher rate of clearance and less adverse events for managing warts.